George F. Kennan an American life - Gaddis, John Lewis (New York Penguin Press, 2011)
Widely and enthusiastically acclaimed, this is the authorized, definitive biography of one of the most fascinating but troubled figures of the twentieth century by the nation's leading Cold War historian. In the late 1940s, George F. Kennan?then a bright but, relatively obscure American diplomat?wrote the "long telegram" and the "X" article. These two documents laid out United States' strategy for "containing" the Soviet Union?a strategy which Kennan himself questioned in later years. Based on exclusive access to Kennan and his archives, this landmark history illuminates a life that both mirrored and shaped the century it spanned.
Includes index
Keywords: Kennan, George F. (George Frost), 1904-2005.